Serum and follicular fluid irisin levels in poor and high responder women undergoing IVF/ICSI - Acet, M.; Celik, N.; Acet, T.; Ilhan, S.; Yardim, M.; Aktun, H. L.; Aydin, S. (Verduci Publisher, 2016)
OBJECTIVE: We examined the follicular fluid (FF) and serum levels of irisin in high and poor responders undergoing IVF/ICSI to test whether irisin has a role in the metabolic regulation of energy homeostasis in growing follicle. PATIENTS AND METHODS: Twenty infertile women with PCOS and 20 poor responder participants undergoing controlled ovarian stimulation (COS) with GnRH antagonist protocol for IVF/ICSI treatment were allocated. Blood was obtained at the time of oocyte retrieval. The follicular fluid content of mature follicles was collected from both high and poor responder women. Irisin levels were measured by using EIA. RESULTS: There was no significant difference between serum and FF-irisin levels in women with PCOS. (11.18 +/- 5.14 mu g/mL vs. 11.06 +/- 4.93 mu g/mL, p < 0.96). In contrast, serum levels of irisin in poor responders were significantly higher than in the FF-irisin levels (13.13 +/- 4.27 mu g/mL vs. 10.09 +/- 4.14 mu g/mL, p < 0.01). FF-irisin levels of PCOS subjects were positively and significantly correlated with serum levels of irisin (r: 0.81, p < 0.00). Serum irisin was positively associated with serum levels of total testosterone but was negatively associated with HOMA-IR in the overall patient population. FF-irisin levels were also noted to be negatively correlated with HOMA-IR. Although there is no correlation between serum irisin and AMH levels, FF irisin levels were negatively correlated with serum AMH levels in PCOS subjects. Contrary to PCOS group there were no significant correlation between serum and FF-irisin levels in poor responder group (r: 0.21; p < 0.35). CONCLUSIONS: The present study is the first attempt to explore the role of irisin in oocyte development by measuring FF and serum levels of this molecules in patients with poor and high responders undergoing IVF/ICSI.
Keywords: PCOS; Poor responder; Serum; Follicular fluid; Irisin